(untitled) (IAHS Medical Journal, 2024)
Background: Percutaneous Nephrolithotomy (PCNL) is the treatment of choice for staghorn stones, large renal stones not amenable to Extra Corporeal Shockwave Lithotripsy (ESWL) and some upper ureteric stones. The success of PCNL is highly related to optimal renal access. Upper calyceal puncture being more difficult and more demanding have relatively few studies presented. The aim of this study was to compare the effectiveness and safety of upper calyceal versus lower calyceal puncture for the removal of complex renal calculi through PCNL. Materials and methods: This hospital-based quasi-experimental study was conducted on admitted patients with complex renal stone who underwent PCNL either by upper calyceal or by lower calyceal approach PCNL technique in the Department of Urology, Chittagong Medical College Hospital and different private hospitals in Chattogram. A total of 75 patients who underwent PCNL were included in the study (37 of them underwent lower calyceal, while 38 underwent upper calyceal puncture). All patients were evaluated to compare the total duration of surgery, intra-operative blood loss, infundibular/ pelvic tear, rate of complete clearance and rate of postoperative complications (Pulmonary, bleeding, fever and sepsis, etc.). SPSS (Statistical Package for Social Science) for Windows version 23 software was used for the analyses. Results: The mean age of the patients was 40.1±11.3 years and 62.67% of them were male. Almost one-third of the patients were obese. The prevalence of hypertension, diabetes and chronic obstructive airway disease was 16%, 6.67% and 6.67%, respectively. The mean size of the stones was for upper and lower calyceal approach was 35.4±5.3 mm and 36.1±6.2 mm, respectively and mostly involved the right kidney. The success rate was similar for upper calyceal and lower calyceal access (89.5% versus 75.7% respectively; p=0.115). Thoracic complications (Hydrothorax and pneumothorax) occurred in 2 patients in upper calyceal access group. Bleeding requiring blood transfusion happened to 5 patients in lower calyceal access and 3 in upper calyceal group (p=0.543). Overall mean operative time and mean length of hospital stay was not significantly different between two groups (p = 0.219 and p=0.603 respectively). Conclusion: Based on the study findings it could be suggested that, there is no significant difference in outcome between upper calyceal and lower calyceal approach for PCNL in patients with complex renal stone. IAHS Medical Journal Volume 6(1), June 2023; 62-67